“Your name does not tick the box”: the intertwining of names, bodies, religion and nationality in the construction of identity within the UK asylum system - Madziva, Roda (Taylor & Francis, 2017)
This article draws on research with Pakistani Christians seeking asylum in the UK, focusing on those with English/biblical names, exploring, firstly the relationship between names and religious persecution in the country of origin, and secondly the complex interaction between names, bodies, religion and nationality within the UK asylum system. It argues that in responding to the perceived threats of immigration and terrorism, British immigration officials tend to use Pakistani as a proxy for Islam, with those Christians who possess English/biblical names often perceived to be a more suspicious group. It concludes by highlighting the need to take religious identities seriously in immigration policies and practices, especially in the context of the current refugee crisis.